INTEGRASI NILAI NILAI ISLAMI MELALUI MEDIA GAMBAR DALAM PEMBELAJARAN MATEMATIKA PADA SISWA: INTEGRATION OF ISLAMIC VALUES THROUGH IMAGE MEDIA IN STUDENTS' MATHEMATICS LEARNING - Lusyana, Evvy; Jundi Mustofa, Muklis (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2024)
Integrating Islamic teachings in learning through image media is an innovative approach. The aim of this research is to examine the application of the integration of Islamic values through image media and its impact on students' understanding in learning mathematics regarding scales and plans. Descriptive qualitative research method and literature review regarding the integration of Islamic teachings in mathematics. The research subjects were education and there were 30 class V students at SDIT AlIslam Sine Ngawi. Data collection methods are interviews, observation, documentation and student assessment questionnaires regarding image media. The research results show that linking mathematics learning with Islamic teachings through image media can increase students' understanding and motivation regarding mathematical concepts. Through this integration, they strengthen the religious values associated with mathematics in their daily lives. The results of the questionnaire assessment showed that the highest score was 50, the lowest score was 32 and the average score was 37.90. This value is classified as quite good. This research provides an important reference for developing mathematics learning media for students that focuses on their cognitive aspects and spiritual values.